Evaluating nitric oxide produced by rat inflamed microglial cell Lline, CHME-5, under the effect of IMOD - Wu, Yu-Wei; Long, Jun-Yao; Liu, Xiao-Gang; Fan, Hong-Qiao (Cellular and Molecular Biology, 2021)
Nitric oxide (NO), as a free radical, is produced by inflamed microglia cells and is one of the destructive factors of the immune system and a factor in myelin degradation. Therefore, inhibition of microglia activity is a chief strategy in reducing neurotoxic damage to the central nervous system. In this study, an herbal Immunomodulatory Drug (IMOD) was used to evaluate the effects of this drug in controlling the amount of nitric oxide. Nitric oxide induction was performed by bacterial lipopolysaccharide (LPS) in rat inflamed microglial cell line, CHME-5. ELISA test was used to measure the produced nitric oxide at 24, 48, and 72 hours. The results showed that the high concentrations of IMOD (1.2, and 4% V/V) had anti-inflammatory effects on microglial cells and were able to reduce the amount of nitric oxide in these cells but the effective dose of IMOD was in the range of 1.2% V/V. Therefore, the safest dose and the best time for the effect of IMOD on inflammatory cell groups are 1.2% V/V and 72h, respectively. Hence, with further studies, IMOD can be considered as an herbal anti-inflammatory drug that is effective in controlling neurodegenerative diseases.